Biological control products for aflatoxin prevention in Italy: commercial field evaluation of atoxigenic Aspergillus flavus active ingredients - Mauro, A.; García Cela, E.; Pietri, A.; Cotty, P.J.; Battilani, P. (MDPI, 2018)
Since 2003, non-compliant aflatoxin concentrations have been detected in maize produced in Italy. The most successful worldwide experiments in aflatoxin prevention resulted from distribution of atoxigenic strains of Aspergillus flavus to displace aflatoxin-producers during crop development. The displacement results in lower aflatoxin concentrations in harvested grain. The current study evaluated in field performances of two atoxigenic strains of A. flavus endemic to Italy in artificially inoculated maize ears and in naturally contaminated maize. Co-inoculation of atoxigenic strains with aflatoxin producers resulted in highly significant reductions in aflatoxin concentrations (>90%) in both years only with atoxigenic strain A2085. The average percent reduction in aflatoxin B1 concentration in naturally contaminated maize fields was 92.3%, without significant differences in fumonisins between treated and control maize. The vegetative compatibility group of A2085 was the most frequently recovered A. flavus in both treated and control plots (average 61.9% and 53.5% of the A. flavus, respectively). A2085 was therefore selected as an active ingredient for biocontrol products and deposited under provisions of the Budapest Treaty in the Belgian Co-Ordinated Collections of Micro-Organisms (BCCM/MUCL) collection (accession MUCL54911). Further work on development of A2085 as a tool for preventing aflatoxin contamination in maize produced in Italy is ongoing with the commercial product named AF-X1™.